Deepening College Students' Engagement with Religion and Theology through Community Service Learning - Seider, Scott (Teaching theology and religion, 2011)
The Serve Program at Ignatius University combines academic study of theology with a year-long community service project focused on combating poverty. An analysis of the Serve Program during the 2008–09 academic year revealed that participating students demonstrated a significant increase in their interest in theology; a greater desire to enroll in theology coursework; and a deeper interest in theology than classmates not participating in the service-learning program. Interviews with Serve participants revealed that their exposure to poverty and inequality through their service placements led them to read the program's assigned theological texts with a particular focus on the authors' messages about individual and social responsibility for struggling fellow citizens.